Peran Brand Management Terhadap Loyalitas Konsumen Untuk Perkembangan Usaha Mikro Kecil Menengah (UMKM) : Suatu Kajian Literatur - Hanifa Sri Nuryani (Pusat Riset dan Inovasi Nasional, 2024)
The role of brand management on consumer loyalty for the development of micro, small and medium enterprises is that brands build a good image among the public. The process is the goal of developing brand identity. This shows that the product offered is a unique product. In addition, it also talks about what kind of identity a brand wants to display. The identity that is displayed will later be attached as the personality of a brand. If the brand has been well received, MSME business actors automatically get the opportunity to improve the quality of their products. This must be done with flexible, effective, efficient, and sustainable planning. Thus, the products produced are guaranteed quality. With guaranteed product quality, consumer loyalty will also increase. After achieving customer satisfaction, the brand must continue to guarantee the improvement and improvement of product quality. The goal is to maintain customer satisfaction. Small businesses get the opportunity to make closer observations and research. This means that MSME business actors get easier and wider access to information. Finally, MSME players are able to produce quality products in accordance with consumer expectations.